2016
DOI: 10.1148/radiol.2015150982
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Left Ventricular Remodeling and Age Assessed with Cardiac MR Imaging: The Multi-Ethnic Study of Atherosclerosis

Abstract: ).q RSNA, 2015 Purpose:To evaluate age-related left ventricular (LV) remodeling during longitudinal observation of a large cohort of asymptomatic individuals who were free of clinical cardiovascular disease at baseline. Materials and Methods:The applicable institutional review boards approved this study, and all participants gave informed consent. Cardiac magnetic resonance (MR) imaging was used to identify longitudinal changes in LV structure and function in 2935 participants who underwent baseline and fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
58
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 38 publications
13
58
1
2
Order By: Relevance
“…31,32 Similarly, obesity has been found to be associated with increased LV mass and decreased LV volumes. 33 While no differences were detected regarding the prevalence of dyslipidaemia and smoking between males and females in our study, we observed that women had a lower BMI than men, and a significant decrease in BMI with increasing age was seen in males but not in females. However, BMI was not found to have significant independent influence on LVEF in our study, thus, the observed gender-specific changes in LV systolic function occurring with advancing age do not seem to depend on an increase in BMI.…”
Section: Discussioncontrasting
confidence: 89%
“…31,32 Similarly, obesity has been found to be associated with increased LV mass and decreased LV volumes. 33 While no differences were detected regarding the prevalence of dyslipidaemia and smoking between males and females in our study, we observed that women had a lower BMI than men, and a significant decrease in BMI with increasing age was seen in males but not in females. However, BMI was not found to have significant independent influence on LVEF in our study, thus, the observed gender-specific changes in LV systolic function occurring with advancing age do not seem to depend on an increase in BMI.…”
Section: Discussioncontrasting
confidence: 89%
“…As shown in [53], this may not be a valid assumption. Hence, future validation of this approach by use of longitudinal data is needed in order to draw clinical conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…21 It would be appealing to combine complementary cardiac magnetic resonance data sets from the MESA cohort, including feature-tracking for strain assessment in each axis, to establish a comprehensive picture of longitudinal adaptations in LV mass, function, and aortic stiffness-findings that may not always be congruent with cross-sectional associations. 22 The right heart is also an important determinant of outcome in heart failure, and there is emerging evidence that a similar relationship exists between pulmonary artery stiffness and right ventricular function to that observed in the systemic circulation. 23 Convincing data are still required on the putative feedback mechanisms between aortic and ventricular dysfunction, what processes might initiate and amplify the progression to heart failure in the general population, or any certainty as to whether outcomes in heart failure may be improved by modifying aortic elasticity independent of conventional risk factors.…”
Section: O'reganmentioning
confidence: 98%
“…21 It would be appealing to combine complementary cardiac magnetic resonance data sets from the MESA cohort, including feature-tracking for strain assessment in each axis, to establish a comprehensive picture of longitudinal adaptations in LV mass, function, and aortic stiffness-findings that may not always be congruent with cross-sectional associations. 22 The right heart is also an important determinant of outcome in heart failure, and there is emerging evidence that a similar relationship exists between pulmonary artery stiffness and right ventricular function to that observed in the systemic circulation. …”
mentioning
confidence: 98%